Questing Role of Landscaping on the Visual Quality of Public Indoor Spaces Based on the User Reactions: Case of Restaurants - Oduncu, Cemile (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Nature is a crucial part of human life. Indoor landscaping is getting more important in today's conditions. Nature integration into the indoor spaces provides various benefits for the interior spaces and the users. In addition to psychological benefits that improve human mood, increase productivity, and give positive emotions to the users, it contributes to the ecological, physical/visual quality of spaces. Therefore, opinions of the users on indoor landscaping are essential. The majority of people spend most of their time indoors, such as homes, offices, and restaurants. This situation causing them to live far from the natural world. Hence, getting away from nature creates the need to integrate nature into the interior spaces. Restaurants are among the most preferred public indoors. Conducting a research on user opinions/reactions on interior landscaping in restaurant spaces, and a literature review on this subject will contribute to this field. It has been identified that the indoor landscaping issue is not given enough significance and a limited number of indoor landscape solutions are preferred for nature integration into spaces at today's restaurant indoors. Thus, this thesis primarily aims to explore, the integration of nature into the selected restaurants that were preferred by various users by conducting a qualitative methodology. And the other aim of this study is to provide landscape integration suggestions that would assist interior designers while integrating natural elements into public interiors, based on the opinions/reactions of different users. The findings of this research were obtained based on the results of the investigations/analysis of selected cases (restaurants) and the detection of user comments/reactions from several digital platforms. Accordingly, various spatial articulation of landscape elements has been detected as well as appreaciative reactions of users upon existing solutions besides positive reactions towards alternate spatial articulations, use of natural materials and use of landscaping elements within the interior space. Keywords: Indoor Landscaping, User Reactions, Nature in the Space, Restaurant

ÖZ:Doğa, insan yaşamının çok önemli bir parçasıdır. Günümüz koşullarında iç mekan peyzajı tasarımının önemi günden güne artmaktadır. İç mekanlara doğa entegrasyonu kullanıcıya ve iç mekanlara bir çok fayda sağlamaktadır. İnsanların ruh halini iyileştiren, verimliliğini artıran ve kullanıcılara olumlu duygular sağlayan psikolojik faydaların yanı sıra mekanların ekolojik, fiziksel/görsel kalitesine de katkı sağlar. Bu nedenle peyzaj elemanlarının iç mekana entegre edilmesi ile ilgili kullanıcı görüşleri önem kazanmaktadır. İnsanlar zamanlarının çoğunu evler, ofisler ve restoranlar gibi kapalı alanlarda geçiriyor. Bu durum insanların doğal dünyadan uzak yaşamalarına neden oluyor. Dolayısıyla doğadan uzaklaşmak doğayı iç mekanlara entegre etme ihtiyacını yaratmaktadır. En çok tercih edilen kamusal alanlar arasında restoranlar yer almaktadır. Böylece, restoran mekanlarında iç mekan peyzaj tasarımı ile ilgili kullanıcı görüşleri/tepkileri üzerine bir araştırma yapılması ve bu konuda literatür taraması yapılması bu alana katkı sağlayacaktır. Günümüz restoran iç mekanlarında peyzaj tasarımı konusuna yeterince önem verilmediği ve peyzaj elemanlarının bu mekanlarda yetersiz kullanıldığı ve ayrıca doğanın iç mekanlara entegrasyonunda sınırlı sayıda iç mekan peyzaj çözümünün tercih edildiği gözlemlenmiştir. Restoran mekanlarında iç mekan peyzaj tasarımına ilişkin farklı kullanıcıların görüşlerini tespit etmek bu konuyu geliştirmek için önemlidir. Bu tez öncelikle doğanın iç mekanlara entegrasyonunu, özellikle çeşitli kullanıcılar tarafından tercih edilen restoranlara entegrasyonunu nitel metodoloji yöntemi ile vi araştırmayı amaçlamaktadır. Bu çalışmanın bir diğer amacı da, farklı kullanıcıların fikirlerine/tepkilerine dayanarak, iç mimarların kamusal iç mekanlara peyzaj elemanlarını entegre ederlerken gözetecekleri peyzaj entegrasyon önerilerini sunmaktır. Bu araştırmanın bulguları, seçilen restoran mekanlarının inceleme/analiz sonuçlarına ve belirlenen dijital platformlardan elde edilen kullanıcı tepki/yorumlarının tespitine dayanılarak elde edilmiştir. Çalışma sonucunda, restoran iç mekanlarında peyzaj elemenlarının farklı entegrasyon yöntemleri tespit edilmiş ve bu çözümlere yönelik kullanıcıların olumlu yorumlar yaptığı belirlenmiştir. Yorumlar bu tür mekanlarda peyzaj elemanlarının kullanımı ve doğa ile bağlantı kurmanın olası yöntemlerine ilişkin de yol gösterici olmuştur. Anahtar Kelimeler: İç Mekan Peyzaj Tasarımı, Kullanıcı Görüşleri, Mekanda Doğa Kavramı, Restoran.
Master of Science in Interior Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2020. Supervisor: Assoc. Prof. Dr. Nil Paşaoğluları Şahin.
Keywords: Landscape Architecture-Landscaping-DesignSubject term:Architecture-landscapes; Indoor Landscaping; User Reactions; Nature in the Space; Restaurant; Landscape; Interior Landscape; Indoor and Outdoor Relationship